(untitled) (Zaporizhzhia Historical Review, 2021)
The young Russian social-democracy was only getting stronger. It used the richest experience of the social democracy of the Europe in such conditions. The edition of the works of the famous people of the German social democracy by the foreign groups RSDRP this was one of the ways of using the knowledge of this party.